Synthesis, Characterization, Conductivity and Investigation of Antimicrobial and Fungus of Magnetic Polymer Including Schiff Bases - Sari, Nursen; Nartop, Dilek; Logoglu, Elif (Asian Journal of Chemistry, 2010)
Novel poly-Schiff base derived from the condensation reaction poly(acrylamide) and 2,2'-bipridine-4,4'-dicarboxaldehyde has been synthesized. -CH=N- and -NH2 group 1H NMR signals were made use of to determine the relative abundance of Schiff base and acrylamide groups in the modified polymer. Metal-aldehyde complexes ([Ni-L], [Co-L], [Mn-L], [Fe-L], [Cr-L]) were anchored poly(acrylamide). PAAm-Schiff base and its metal complexes were characterized by magnetic susceptibility, electronic and spectral studies. The DC conductivities of the solid samples were measured using a four-probe technique. The conductivity of coordination polymers were found to be high in comparison to PAAm including Schiff bases. In vitro activities against some Gram-positive (Bacillus subtillis, Bacillus cereus, Micrococcus luteus NRLL B4375, Pseudomonas aeroginosa ATCC 29212) and the fungus Candida albicans were determined.